2017
DOI: 10.1002/eat.22726
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of premature termination from psychotherapy for anorexia nervosa: Low treatment credibility, early therapy alliance, and self‐transcendence

Abstract: Routine assessment of treatment credibility and early process (comprehensively assessed from multiple perspectives) may help clinicians reduce PTT thereby enhancing treatment outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
11
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 24 publications
3
11
0
1
Order By: Relevance
“…Moreover, those who did not complete the end of intervention assessment showed a trend toward more frequent purging behaviors. These findings confirm the importance of considering patient-and early process-related variables when delivering technology-based interventions (Kelders et al, 2012) and are consistent with the literature indicating that low treatment credibility and poor early alliance with the therapist are associated with premature termination of treatment (Jordan et al, 2017). The poorer quality of the relationship with the mentor found in the group of non-completers is particularly important when considering the specific characteristics of RecoveryMANTRA.…”
Section: Discussionsupporting
confidence: 87%
“…Moreover, those who did not complete the end of intervention assessment showed a trend toward more frequent purging behaviors. These findings confirm the importance of considering patient-and early process-related variables when delivering technology-based interventions (Kelders et al, 2012) and are consistent with the literature indicating that low treatment credibility and poor early alliance with the therapist are associated with premature termination of treatment (Jordan et al, 2017). The poorer quality of the relationship with the mentor found in the group of non-completers is particularly important when considering the specific characteristics of RecoveryMANTRA.…”
Section: Discussionsupporting
confidence: 87%
“…In other words, patients who might not profit from early symptom change may instead be the ones who drop out of studies, leading to a potential bias in estimating the effect of early symptom change on TA. Supporting this hypothesis, our review found support for the predictive effect of TA on completion of treatment [45,46,57]. On the other hand, some studies failed to find a predictive effect of TA on completion [44,58,63,71].…”
Section: Integration With Previous Research and Suggestions For Further Researchsupporting
confidence: 61%
“…Five articles analyzing four samples looked into the influence of TA on treatment outcome of adult patients suffering from AN [44][45][46][47][48]. Three of those samples received outpatient treatment, and one study took place in an inpatient setting.…”
Section: Anorexia Nervosa: Adultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite these strengths, study results should be interpreted in light of some limitations. Although the sample allowed investigation of NES in a novel way within a clinically diagnosed ED sample, the current sample had a different pro le of personality traits, including higher harm avoidance, than the general population, as has been found with other ED samples [39]. Personality is believed to be relatively stable during a person's lifetime [40], so it could be hypothesised that NES may be a consequence of particular personality traits.…”
Section: Strengths and Limitationsmentioning
confidence: 89%